Odpowiedź :
2x(-2+0,3x)=-4x+0,6x i tan x na kocu do kwadratu
3(-a+4)-½(6-a)=-3a+12-3+0,5a=3,5a+9
(2x-3)(x+7)=13x-21
(4-5)(1-6y)=-1+6y
więcej niestety nie wiem
3(-a+4)-½(6-a)=-3a+12-3+0,5a=3,5a+9
(2x-3)(x+7)=13x-21
(4-5)(1-6y)=-1+6y
więcej niestety nie wiem
2x(-2+0,3x)=-4x+0.6x²=x(-4+0.6x)
3(-a+4)-½(6-a)=-3a+12-3+½a=9-2½a
(2x-3)(x+7)=2x²+11x-21
(4-5)(1-6y)=4-24y-5+30y=6y-1
-5(0,4√7-1,2√5)=-2√7+6√5=2(3√5-√7)
√3(2√3-3)=6-3√3=3(2-√3)
3(-a+4)-½(6-a)=-3a+12-3+½a=9-2½a
(2x-3)(x+7)=2x²+11x-21
(4-5)(1-6y)=4-24y-5+30y=6y-1
-5(0,4√7-1,2√5)=-2√7+6√5=2(3√5-√7)
√3(2√3-3)=6-3√3=3(2-√3)